(untitled) (Journal of Applied Membrane Science & Technology, 2021)
Forward osmosis (FO) is an osmotically driven membrane separation process. It is potentially applied in various industries for nutrient recovery and water reclamation. Although FO showed a lesser fouling tendency than other pressure-driven membrane processes, the solutes in the feed solution would still deposit on the membrane surface, forming a fouling layer that resists water permeation. For that reason, fouling mitigation is a trending issue in the FO process. A better understanding of the fouling mechanism is required before opting for the appropriate strategy to mitigate it. This article describes the fouling mechanism based on different foulant presented in the feed, followed by a method in relieving fouling in the FO process.